O Bilinguismo de surdos mediado por diálogos no Orkut - Grassi, Dayse (2010)
This study is briefly configured to present an interpretive nature survey, of the case study type, and it proposes Orkut analysis of deaf people. Through the "digital conversations" deaf people gave a new meaning to the Portuguese language learning, so as to be seen as necessary to promote communication with their friends, shortening distance and time. Thus, we analyze in this research, issues related to the deaf identity, deaf culture, signs language, the Portuguese writing and bilingualism of deaf people. The survey data were collected from deaf people through Orkut profile of each of them, the Orkut communities which include the posts left on Orkut. Thus, we checked the Orkut communities which the deaf person belongs, the issue of bilingualism for the deaf and if the deaf people see themselves as bilingual and, finally, in posts / dialogues in Orkut, we analyzed if the writing of deaf people in Portuguese has some specificity, the Portuguese written by these people is similar or different from the listeners, if the writing of these people is presented in Portuguese or "internet language" and what that means for deaf people. In this sense, we are concerned to place the reader on deafness and deaf people, showing the deaf people as a minority group, possessing a unique culture that sustains peculiar aspects: history, life experiences, identity, an own language the Libras , which substance 'sign' generates a spatial-visual modality, a peculiar way of seeing the world. Thus, the deaf people are immersed in the same physical space as the listeners, sharing mixed cultures, moving through two languages - the language of signs and the Portuguese language - thus building a peculiar form of writing, in a not typical context of bilingualism.